2023
DOI: 10.1051/0004-6361/202245645
|View full text |Cite
|
Sign up to set email alerts
|

Extended atomic data for oxygen abundance analyses

Abstract: As the most abundant element in the universe after hydrogen and helium, oxygen plays a key role in planetary, stellar, and galactic astrophysics. Its abundance is especially influential in terms of stellar structure and evolution, and as the dominant opacity contributor at the base of the Sun's convection zone, it is central to the discussion on the solar modelling problem. However, abundance analyses require complete and reliable sets of atomic data. We present extensive atomic data for O i by using the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Their result is also in agreement with those of Magg et al (2022) and GS98. However, the analyses of Li et al (2021Li et al ( , 2023bLi et al ( , 2023a found that the abundances of carbon, nitrogen, and oxygen are only marginally higher than those given by Amarsi et al (2021). Pietrow et al (2023) also obtained an oxygen abundance that is between that of Amarsi et al (2021) and that of Magg et al (2022).…”
Section: Introductionmentioning
confidence: 81%
“…Their result is also in agreement with those of Magg et al (2022) and GS98. However, the analyses of Li et al (2021Li et al ( , 2023bLi et al ( , 2023a found that the abundances of carbon, nitrogen, and oxygen are only marginally higher than those given by Amarsi et al (2021). Pietrow et al (2023) also obtained an oxygen abundance that is between that of Amarsi et al (2021) and that of Magg et al (2022).…”
Section: Introductionmentioning
confidence: 81%
“…That, in turn, depends on two elements, oxygen and iron, that determine about half of the solar opacity at BCZ. However, a downward revision of oxygen abundance by up to 20-40% from earlier solar composition is a major part of the "solar problem" (Asplund et al (2021); Pietrow et al (2023); Li et al (2023); Buldgen et al (2023b). Since about 90% of oxygen is either fully ionized or H-like at BCZ, its absorption coefficient is small and unlikely to change from current atomic calculations, enhanced iron opacity might countenance lower solar abundances (Bailey et al (2015).…”
Section: Introductionmentioning
confidence: 99%